Effectiveness Implementation of The Practical Instrument to Assess The Ability of Affective and Psychomotor Aspects Pre-Service Chemistry Education Teacher Students in Laboratory Activities - Mujakir, Mujakir (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
In the practicum activities, there is still a lack of implementation time, due to ineffective instruments and work procedures. The purpose of this study was to determine the effectiveness of laboratory activity instruments on affective and psychomotor aspects. This study employs a quantitative descriptive approach in its survey design. The sample of the study consisted of students from the Chemistry Education Study Program, Faculty of Tabiyah and Teacher Training Ar-Raniry State Islamic University, Banda Aceh, in their third semester, who were taking practicum courses. There were 35 students, three lecturers teaching practicum courses, and two laboratory assistants. The data obtained were described quantitatively. The results showed that (a) the average student response to the use of the instrument was strongly agree 54.08%, agree 44.38%, and disagree 10.77%. In the affective aspect, the number of aspects that emerged ranged from 6 to 18 aspects within 100 minutes, while the number of aspects in psychomotor aspects ranged from 8 to 26 within the same 100-minute activity span. Based on these results, it was concluded that the practicum activity instrument was effective in assessing the affective and psychomotor aspects of students in practicum activities.